Pathological Basis for Deficient Excitatory Drive to Cortical Parvalbumin Interneurons in Schizophrenia - Chung, Daniel W; Fish, Kenneth N; Lewis, David A (The American journal of psychiatry, 2016)
Objective:Deficient excitatory drive to parvalbumin-containing cortical interneurons is proposed as a key neural substrate for altered gamma oscillations and cognitive dysfunction in schizophrenia. However, a pathological entity producing such a deficit has not been identified. The authors tested the hypothesis that cortical parvalbumin interneurons receive fewer excitatory synaptic inputs in individuals with schizophrenia.Method:Fluorescent immunohistochemistry, confocal microscopy, and post-image processing techniques were used to quantify the number of putative excitatory synapses (i.e., the overlap of vesicular glutamate transporter 1-positive [VGlut1+] puncta and postsynaptic density protein 95-positive [PSD95+] puncta) per surface area of parvalbumin-positive (PV+) or calretinin-positive (CR+) neurons in the dorsolateral prefrontal cortex from schizophrenia subjects and matched unaffected comparison subjects.Results:Mean density of VGlut1+/PSD95+ puncta on PV+ neurons was 18% lower in schizophrenia, a significant difference. This deficit was not influenced by methodological confounds or schizophrenia-associated comorbid factors, not present in monkeys chronically exposed to antipsychotic medications, and not present in CR+ neurons. Mean density of VGlut1+/PSD95+ puncta on PV+ neurons predicted the activity-dependent expression levels of parvalbumin and glutamic acid decarboxylase 67 (GAD67) in schizophrenia subjects but not comparison subjects.Conclusions:To the authors’ knowledge, this is the first demonstration that excitatory synapse density is lower selectively on parvalbumin interneurons in schizophrenia and predicts the activity-dependent down-regulation of parvalbumin and GAD67. Because the activity of parvalbumin interneurons is required for generation of cortical gamma oscillations and working memory function, these findings reveal a novel pathological substrate for cortical dysfunction and cognitive deficits in schizophrenia.